Alcoholism in the family context: confronting strategies of the older users of comunity therapy - Filha, Maria de Oliveira Ferreira; Sá, Aralinda Nogueira Pinto de; Rocha, Ianine Alves da; Silva, Vagna Cristina Leite da; Souto, Claudia Maria Ramos Medeiros; Dias, Maria Djair (Rev Rene, 2012)
Alcoholism in the family context poses significant risks to older women who become the most common victims of this problem. This is a documentary study aiming to identify the confronting strategies of alcoholism used by older women, in the family and spontaneous comments expressed at the last moment in the Community Therapy circles held at the Health Department in João Pessoa - PB, in July 2008. For this research 776 Community Therapy information sheets were checked. The findings were organized in the form of narratives and separated into analytical compiled categories. That demonstrated how the most used strategies: spirituality (33,3%), self-help groups (26,6%) and strengthening of family (13,3%); and more frequent statements: courage (15.5%), hope (13.3%), faith (11.1%), trust and unity (6.6%) are in line with the analytical categories, functioning as a master spring in the process of empowerment, by strengthening bonds and creating resilience, thereby allowing the family to overcome the daily dilemmas, and face the problem of alcoholism.